2021
DOI: 10.1136/jech-2020-215574
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community interventions for protecting and promoting the mental health of working-age adults experiencing financial uncertainty: a systematic review

Abstract: BackgroundThe COVID-19 pandemic has created a period of global economic uncertainty. Financial strain, personal debt, recent job loss and housing insecurity are important risk factors for the mental health of working-age adults. Community interventions have the potential to attenuate the mental health impact of these stressors. We examined the effectiveness of community interventions for protecting and promoting the mental health of working-age adults in high-income countries during periods of financial insecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Studies were excluded if participants had serious mental illness, were not of working age, were part of a specific group (e.g., single mothers), or were focused on rehabilitation into the workforce for those with serious physical or mental health problems. Despite overlap in the search period, only two studies overlapped with the previous review by McGrath et al (68) (one assessing debt advice hotline, and one assessing a group job skills training intervention). This review found, based on multiple trials, intensive 1-to-2-week job skills and self-efficacy training ("job clubs") were effective in reducing depression for up to 2 years.…”
Section: Individual Level Interventions Addressing Employment and Per...mentioning
confidence: 99%
“…Studies were excluded if participants had serious mental illness, were not of working age, were part of a specific group (e.g., single mothers), or were focused on rehabilitation into the workforce for those with serious physical or mental health problems. Despite overlap in the search period, only two studies overlapped with the previous review by McGrath et al (68) (one assessing debt advice hotline, and one assessing a group job skills training intervention). This review found, based on multiple trials, intensive 1-to-2-week job skills and self-efficacy training ("job clubs") were effective in reducing depression for up to 2 years.…”
Section: Individual Level Interventions Addressing Employment and Per...mentioning
confidence: 99%
“…Moreover, the acute phase of the present crisis, and its long-term consequences, tend to show that the disruption of mental health must be regarded as a significant threat. Community interventions may also address the mental health inequalities issue, but need more evidence-based studies (see McGrath et al, 2021 for a review). As suggested by Ridley et al (2020), future interventions to limit the negative impact of the COVID-19 pandemic and its direct consequences are much needed, and financial insecurity seems to be an important variable to include as suggested by the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Research has evaluated the impact of Cognitive Behavioral Therapy (CBT) in those who are unemployed, with mixed results about effectiveness ( 32 ). There has also been some research on community based interventions such as debt advice, social prescribing and labor market programmes, however there is not much evidence about the impact of this on mental health ( 33 ). Internet-delivered CBT (iCBT) has been shown by several meta-analyses to be effective for symptoms of depression and anxiety ( 34 38 ), and represents a way to increase access to psychological interventions.…”
Section: Introductionmentioning
confidence: 99%